The politics of counterterrorism in India : strategic intelligence and national security in South Asia. - Mahadevan, Prem. (London : I.B.Tauris, 2012)
Combining a theoretical approach with empirical analysis of India's counterterrorist activities, this book holds valuable information for those examining strategy-making and counterterrorism - practitioners as well as researchers - in addition to those interested in the politics of India.